In vitro maintenance, under slow-growth conditions, of oil palm germplasm obtained by embryo rescue - Julcéia Camillo; Jonny Everson Scherwinski-Pereira (Pesquisa Agropecuária Brasileira, 2015)
The objective of this work was to evaluate the in vitro maintenance of oil palm (Elaeis guineensis and E. oleifera) accessions under slow-growth conditions. Plants produced by embryo rescue were subject to 1/2MS culture medium supplemented with the carbohydrates sucrose, mannitol, and sorbitol at 1, 2, and 3% under 20 and 25±2ºC. After 12 months, the temperature of 20°C reduced plant growth. Sucrose is the most appropriate carbohydrate for maintaining the quality of the plants, whereas mannitol and sorbitol result in a reduced plant survival.